2021
DOI: 10.3390/educsci11080442
|View full text |Cite
|
Sign up to set email alerts
|

Learning and Well-Being in Educational Practices with Children and Adolescents Undergoing Cancer Treatment

Abstract: The use of information communication technologies (ICT) in education brings up new possibilities of promoting learning and health experiences. In this sense, education contexts of the 21st century must consider these two areas of knowledge, especially their integration. This article presents learning practices developed with mobile devices and games in order to improve learning and well-being in children and adolescents undergoing cancer treatment in a non-formal educational setting. The methodology is based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 63 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…There was one study found in North American and African regions, respectively. As to the distribution by country, the highest number of studies were conducted in Portugal [20], [29], [30] and Brazil [24], [26], [33] with n=3 studies respectively. Meanwhile, nine countries, namely Finland [19], Costa Rica [21], Nigeria [22], Greece [23], Romania [32], Luxembourg [25], Ireland [27], Spain [31], and a combination of respondents from both Bangladesh and Pakistan [28] were recorded with one study each.…”
Section: Distribution Of Past Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…There was one study found in North American and African regions, respectively. As to the distribution by country, the highest number of studies were conducted in Portugal [20], [29], [30] and Brazil [24], [26], [33] with n=3 studies respectively. Meanwhile, nine countries, namely Finland [19], Costa Rica [21], Nigeria [22], Greece [23], Romania [32], Luxembourg [25], Ireland [27], Spain [31], and a combination of respondents from both Bangladesh and Pakistan [28] were recorded with one study each.…”
Section: Distribution Of Past Studiesmentioning
confidence: 99%
“…From the accumulated 15 studies in Table 4, n=10 [20], [23]- [24], [26], [27], [29], [30]- [33] were qualitative studies, followed by n=3 [21], [22], [25] were quantitative studies. Meanwhile, n=2 studies [19], [28] used a mixed-method research design.…”
Section: Research Design Used In Past Studiesmentioning
confidence: 99%
See 3 more Smart Citations